2009
DOI: 10.1073/pnas.0910125106
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nanoparticles of blue haze enhanced by anthropogenic pollution

Abstract: The molecular processes leading to formation of nanoparticles of blue haze over forested areas are highly complex and not fully understood. We show that the interaction between biogenic organic acids and sulfuric acid enhances nucleation and initial growth of those nanoparticles. With one cis-pinonic acid and three to five sulfuric acid molecules in the critical nucleus, the hydrophobic organic acid part enhances the stability and growth on the hydrophilic sulfuric acid counterpart. Dimers or heterodimers of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
245
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 246 publications
(259 citation statements)
references
References 37 publications
13
245
1
Order By: Relevance
“…While the water effects on particle growth are taken into account in equation (2) since W R is dependent on RH, growth by ammonia is not considered here. Recent studies have showed that ammonia does not effectively contribute to aerosol growth [Zhang et al, 2009], and the condensation of (NH 4 ) 2 SO 4 can be in fact similar to that of H 2 SO 4 [Weber et al, 1998]. …”
Section: Other Methods To Calculate Growth Rates (Gr)mentioning
confidence: 99%
See 2 more Smart Citations
“…While the water effects on particle growth are taken into account in equation (2) since W R is dependent on RH, growth by ammonia is not considered here. Recent studies have showed that ammonia does not effectively contribute to aerosol growth [Zhang et al, 2009], and the condensation of (NH 4 ) 2 SO 4 can be in fact similar to that of H 2 SO 4 [Weber et al, 1998]. …”
Section: Other Methods To Calculate Growth Rates (Gr)mentioning
confidence: 99%
“…For example, theoretical calculations and observations [Barsanti et al, 2009;Kurten et al, 2008;Smith et al, 2008Smith et al, , 2010 have shown that amines may be involved in J is nucleation rate calculated from PARGAN (that is, J PARGAN ), C is preexponential factor, and P is power, for J = C[H aerosol nucleation in the atmosphere. Laboratory studies also showed that aromatic acids may increase nucleation rates similarly to NH 3 [Zhang et al, 2004] and biogenic organic compounds can enhance aerosol growth rates of H 2 SO 4 aerosols [Zhang et al, 2009].…”
Section: Indirect Chemical Information Of Newly Formed Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). New particle formation typically corresponds to a regional event, and a variety of compounds have been associated with aerosol nucleation, including sulfuric acid, organics, basic species, and preexisting particles (7,(19)(20)(21)(22)(23). There is a noticeable absence of new particle formation as the pollution episode develops, indicating the suppression of nucleation by preexisting particles.…”
Section: Significancementioning
confidence: 99%
“…The exact composition of the surface is therefore relevant to many of the chemical reactions that occur in the atmosphere and that affect climate 13 . In addition, organic molecules serve as cloud condensation nuclei [14][15][16] , and nucleation due to sulphuric acid particles is enhanced by the presence of organic compounds [17][18][19] . Therefore, the effect of organic layers on water aerosols in the atmosphere has been the subject of research for several decades, for reviews on the subject see references [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%